Lack of Agreement of Chromogenic and Glotting Assays for Factor X and Protein C in Warfarinised Plasma - Han, P; Fung, K P; Rahdakrishnan, U (Thrombosis and Haemostasis, 1991)
Coagulation serine proteases can be measured with either a chromogenic substrate assay or a clotting assay using deficient plasmas. It is a concern whether both assays give similar quantitative results, in particular in plasma obtained fiom patients on long term warfarin therapy. If these two assay methods were interchangeable, then the chromogenic substrate assay has the advantages of precision as well as laboratory automation. We used the intraclass correlation coefficient (r1) to assess the agreement between the two methods in measuring factor X and protein C levels in warfarinised plasma. The results indicate that the extent and pattern of agreement of the two methods for the measurement of the two variables in warfarinised plasma are poor, despite high Pearson product moment coefficients of correlation.